Efektivitas Technode Hydrogel 0,02% Sebagai Penyembuhan Luka Post Operasi Ovariohisterectomi dan Orchhiectomi Pada Kucing Domestik (Felis silvestris Catus) Dibandingkan Iodine 10% - Nida Ul Millah; Dian Eka Ermawati (Journal of Applied Agriculture, Health, and Technology, 2022)
Antibiotics have been reduced to support Anti-Microbial Resistance (AMR) campaigns worldwide due to widespread bacterial resistance to commonly used antibiotics, the emergence of new superbugs or diseases, and the impact of antibiotic waste on the environment and soil. Iodine is generally used as an alternative because it has antibacterial and antifungal potential, suitable for preventing wound infections. However, iodine can cause a serous exudative effect and quickly become inactive when mixed with serous fluids. The study aims to find alternative therapeutic preparations to replace antibiotics when treating open wounds. Experimental research in which domestic cats were divided into two groups. Group A was given 10% iodine therapy twice a day, while Group B was given Technode Hydrogel 0,02% therapy twice a day for seven days. The wound score was calculated based on three points with the following criteria: discharge, swelling, erythema, and dehiscence. The scoring system was adopted as suggested by Sylvestre. The results showed that Technode Hydrogel 0,02% had an average wound score of 0,457 compared to 10% iodine which was 0,714. Hydrogel Technode is expected to be the best alternative for wound care, both in terms of efficacy and efficiency, to help the healing process of open wounds.